Matrilysin expression and function in airway epithelium. - Dunsmore, S E (1998)
We report that matrilysin, a matrix metalloproteinase, is constitutively expressed in the epithelium of peribronchial glands and conducting airways in normal lung. Matrilysin expression was increased in airway epithelial cells and was induced in alveolar type II cells in cystic fibrosis. Other metalloproteinases (collagenase-1, stromelysin-1, and 92-kD gelatinase) were not produced by normal or injured lung epithelium. These observations suggest that matrilysin functions in injury-mediated responses of the lung. Indeed, matrilysin expression was increased in migrating airway epithelial cells in wounded human and mouse trachea. In human tissue, epithelial migration was reduced by > 80% by a hydroxamate inhibitor, and in mouse tissue, reepithelialization in trachea from matrilysin-null mice was essentially blocked. In vivo observations and cell culture studies demonstrated that matrilysin was secreted lumenally by lung epithelium, but upon activation or while migrating over wounds, some matrilysin was released basally. The constitutive production of matrilysin in conducting airways, its upregulation after injury, its induction by alveolar epithelium, and its release into both lumenal and matrix compartments suggest that this metalloproteinase serves multiple functions in intact and injured lung, one of which is to facilitate reepithelialization.